FAKTOR- FAKTOR YANG MEMENGARUHI SERVICE PER CONCEPTION SAPI PERAH PADA PETERNAKAN RAKYAT DI PROVINSI LAMPUNG - Ertha Colanda Sari; Madi Hartono; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The aims of this research were to know factors and values of the factors that influence of service per conception of dairy cattle on the people’s farm at Lampung Province on Juni-July 2016. Analysis for this research is multiple regression analysis with spss (statistic packet for social science) program. The results of this research indicate that service per conception (S/C) of dairy cattle in the province of lampung are 2.09 ± 1.28. Factors affecting the value of S/C from the farmer and the cattles. On the level of farmer are have already trained that negatively associated with factor value 5.891, farmer knowledge that positively associated with factor value 5.517, total concentrate supplied that positively associated with factor value 0.193, and water supply system that negatively associated with factor value 1.471. factor affecting S/C on dairy cattle are lactation length that negatively associated with factor value 0.065 and reproduction disturbance that positively associated with factor value 2.814. Keywords: Service per Conception, Dairy Cattle, Public Farm, Lampung Province